Evolutionary and structural basis of SLAMF1 utilization in morbilliviruses—Implications for host range and cross-species transmission - Hyodo, Ayumu; Seki, Fumio; Fukuda, Kento; Tashiro, Kaede; Kitai, Yuki; Akahori, Yukiko; Watabe, Hideko; Katoh, Hiroshi; Osaki, Rikuto; Takaya, Daisuke; Kawashita, Norihito; Fukuhara, Hideo; et al. (PLoS pathogens, 2025)
Morbilliviruses, including measles virus (MV), canine distemper virus (CDV), peste des petits ruminants virus, and cetacean morbillivirus pose a significant threat to humans and animals. While the host range of morbilliviruses is generally well-defined, cross-species transmission events with significant mortality have also been reported. Their entry into immune cells, the primary targets of morbilliviruses, relies on the signaling lymphocytic activation molecule (SLAM), also known as SLAMF1 or CD150. In this study, we hypothesize that the ability of morbilliviruses to utilize heterologous SLAM receptors stems from evolutionarily conserved structural determinants within the SLAM protein and that minimal genetic changes in the viral receptor-binding H protein can enable adaptation to novel hosts. To test this, we systematically assessed SLAM utilization and adaptation by diverse morbilliviruses. We found that most morbilliviruses efficiently utilize SLAM from multiple host species, including Myotis bat SLAM, but not human SLAM. Only MV could efficiently utilize human SLAM. Additionally, unlike other morbilliviruses, MV utilized Myotis bat SLAM inefficiently. As an example of morbillivirus adaptation to non-host animal SLAM, we conducted an MV adaptation experiment with Myotis bat SLAM. We demonstrated that MV readily adapted to utilize Myotis bat SLAM by acquiring a single N187Y mutation in its hemagglutinin protein. Notably, hypothetical ancestral SLAMs acted as universal receptors for all morbilliviruses. These results reinforced that morbillivirus receptor usage is primarily supported by evolutionarily conserved structural features of SLAM, highlighting a molecular basis that enables morbilliviruses to rapidly adapt to diverse animal SLAMs.